КЕҢЕСБАЙ РАХМАНОВ ПОЭЗИЯСЫНДА ЭПИФОРАЛАРДЫҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Кудайбергенова, Г.П. (FAN va JAMIYAT, 2025)
This article examines the features of using one type of repetition—epiphora—in linguistics and artistic literature. Specifically, examples of the use of epiphoras in the songs of poet K. Rakhmanov are analyzed.